Odonate diversity and community turnover along elevational gradients in the Karnali River Basin, Nepal - Sharma, Manoj; Oli, Buddhi Ram; Gautam, Ishan (Nepalese Journal of Zoology, 2025)
Odonates are bioindicators, and understanding their species composition pattern along elevational gradients is essential for conservation initiatives. This study investigates the diversity and distribution patterns of Odonata along an elevational gradient (544–2987 m above sea level (asl)) in the Karnali River basin of western Nepal. Sampling was conducted across 15 sites during pre-monsoon, monsoon, and post-monsoon seasons of 2022 using the belt transect method in lentic and lotic habitats. The Shannon Diversity Index, Simpson’s Index, and beta (β) diversity (both incidence-based and abundance-based) were used to describe the odonate assemblages. A total of 90 species representing 54 genera and 12 families (five Anisoptera and seven Zygoptera) were recorded. Libellulidae and Coenagrionidae emerged as the most species-rich families among dragonflies and damselflies, respectively. Diversity indices fluctuated with elevation, with the Shannon (3.58) and Simpson (0.96) indices peaking at 646 m and declining sharply at higher altitudes. Polynomial regression revealed a significant negative correlation (r = -0.81, p < 0.001) between species richness and elevation. β-diversity analysis showed high dissimilarity and turnover among sites, with incidence-based dissimilarity (mean β_sor = 0.572) and abundance-based dissimilarity (mean dBC = 0.664) both driven primarily by species turnover. Lentic habitats showed higher β-diversity (mean β_sor = 0.607) than lotic habitats (mean dBC = 0.595). Most species exhibited narrow elevational ranges, primarily below 1600 m, while a few were widespread, including Pantala flavescens, which were recorded from lower to higher elevation ranges. These findings highlight significant spatial variation in odonate assemblages across elevations, underscoring the ecological sensitivity of montane aquatic habitats to altitudinal and potentially climatic gradients.